ADULT EDUCATION AND RURAL SOCIO-ECONOMIC DEVELOPMENT IN NIGERIA - Abba, Mannir (Sokoto Educational Review, 2020)
As Nigeria attempts without much success to pull itself out of rural socio-economic underdevelopment despite its rich variety of natural resources at its disposal. Still the country is unsuccessful in war against illiteracy, poverty, hunger, unemployment, and diseases like malaria, cholera, polio, missiles, HIV/AIDS and environmental problems that hindered most of the rural people in the country. This paper presents a conceptualization of how adult education can be a veritable tool or strategic objective as well as an instrument for rural socio- economic development in the country. Adult education has the potential for improving the quality of life for individuals living in rural areas expanding their access to income and employment opportunities. Adult education is a continuing process where adults, who perform multiple social roles, participate in organized learning activities to improve their human resources skill or their human capital assets.